2018
DOI: 10.1093/femsyr/foy005
|View full text |Cite
|
Sign up to set email alerts
|

Study of the role of the covalently linked cell wall protein (Ccw14p) and yeast glycoprotein (Ygp1p) within biofilm formation in a flor yeast strain

Abstract: Flor yeasts are Saccharomyces cerevisiae strains noted by their ability to create a type of biofilm in the air-liquid interface of some wines, known as 'flor' or 'velum', for which certain proteins play an essential role. Following a proteomic study of a flor yeast strain, we deleted the CCW14 (covalently linked cell wall protein) and YGP1 (yeast glycoprotein) genes-codifying for two cell surface glycoproteins-in a haploid flor yeast strain and we reported that both influence the weight of the biofilm as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Studies of differential protein expression in the course of sherry-wine formation is limited, however recently several reports documenting semi-quantitative proteomic analysis of cytosolic, cell-wall and mitochondrial proteins of industrial flor strain under laboratory "non-biofilm" and "biofilm" conditions have been carried out (Moreno-García et al, 2015, 2018a. These studies revealed alterations in the abundance of proteins involved in respiration, translation, stress damage prevention, DNA reparation, carbon and amino acid metabolism, some interesting finding associated with the changes in abundance of flor yeast enzymes affecting sensory properties of sherry wine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of differential protein expression in the course of sherry-wine formation is limited, however recently several reports documenting semi-quantitative proteomic analysis of cytosolic, cell-wall and mitochondrial proteins of industrial flor strain under laboratory "non-biofilm" and "biofilm" conditions have been carried out (Moreno-García et al, 2015, 2018a. These studies revealed alterations in the abundance of proteins involved in respiration, translation, stress damage prevention, DNA reparation, carbon and amino acid metabolism, some interesting finding associated with the changes in abundance of flor yeast enzymes affecting sensory properties of sherry wine.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylated cell surface proteins, encoded by CCW14 and YGP1, contribute to yeast biofilms. This may result from the hydrophobicity of the two proteins in haploid strains (Moreno-García et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The covalently linked cell wall mannoprotein Ccw14p [ 59 , 60 ] was found in both strains, although its content was more relevant in flor yeast G1 (only identified at T1 under both conditions). Furthermore, deletion of this gene confirmed their role in biofilm formation in flor yeast G1, showing a decrease of the biofilm weight and cell adhesion [ 61 ]. Cwp1p localizes to the birth scars of daughter cells [ 62 ], and Dan4p was obtained in the two yeast strains and specifically in P29, both under NPCT1, respectively.…”
Section: Resultsmentioning
confidence: 98%